SAYYED HOSSEIN NASR: ETIKA DAN MORALITAS DALAM EKONOMI ISLAM - Nasution, Darwin; Afridah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Islamic economics is a growing topic along with the increasing awareness of the importance of Islamic values ​​in various areas of life, including ethics and morals in economics. One of the influential figures in this field is Sayyed Hossein Nasr. Nasr argues that ethics and morality are an important part of human life that distinguishes humans from animals. Ethics are teachings that discuss good and bad, while morals are the limits given to distinguish good or bad human actions, so that in his view of ethics and morals in modern times is a modern scientific worldview that is limited and reductive with it has caused the loss of spiritual and ethical values, he proposed that economic activities in Islamic science should be based on the principles of tawhid, adab, and akhlaq. Meanwhile, in Islamic economics, spiritual and ethical values ​​are a set of moral values ​​and principles that govern economic behavior in Islam. This ethics is based on the teachings of the Qur'an and Hadith as the main guideline. The principles of Islamic economic ethics reflect the goal of Islam to create a just, fair, and moral society.